PENGARUH EXPERIENTIAL MARKETING, KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Survei Pada Pengguna Lazada di Kabupaten Tuban) - RIKA APRILIA; Priscilla Uning; Ahmad Husin (JURNAL WIRANOMIKA, 2024)
Abstract: The growth of e-commerce has brought many changes to the business sector, which was initially based in the physical world before evolving into the virtual realm. Lazada is one of the online shopping sites that is already familiar among e-commerce players through television and internet advertisements. This research aims to determine the influence of experiential marketing, service quality, customer satisfaction, and customer loyalty on customer loyalty. This research is quantitative based on primary data from respondent questionnaires. The sampling in this study used purposive sampling techniques with a total of 95 respondents. The data analysis method used in this research is through multiple linear regression analysis techniques using SPSS software. The research results indicate that Experiential Marketing (X1), Service Quality (X2), and Customer Satisfaction (X3) have an impact on Customer Loyalty (Y) among Lazada users in Tuban Regency. Experiential Marketing (X1) is the most dominant variable affecting customer loyalty (Y) among Lazada users in Tuban Regency.